(untitled) (Fiep Bulletin - online, 2014)
Abstract - Spinning® is a predominantly aeróbic activity carried through in different intensities (Kang et al, 2005) on a stationary bicycle. It is an activity of great success in the academies nowadays, mainly for being considered of great energy expense - around 458 kcal (LIMA et al, 2003), enclosing diverse public. Purpose: To verify which is the situation of bigger cardiac overload being compared the rate-pressure product during the works of slow cadence (65 - 85 RPM) with much overload and fast cadence (100 - 120 RPM) with little overload during the spinning®. Relevance: importance of verifying which type of work must be prevented and which maneuvers can be stimulated during spinning® classes.